Penerbitan PERPPU Penanganan Pandemi Covid-19 sebagai Hak Prerogatif Presiden dalam Perspektif HTN - Marasutan (Inovasi Pratama Internasional. Ltd, 2022)
The President is the highest state government administrator and in carrying out state government the power and responsibility are in the hands of the President. The formulation of the problem in this study is how the President's prerogative is to issue government regulations in lieu of the law on handling the Covid-19 pandemic, how is the President's power in issuing PERPPU for Handling the Covid-19 Pandemic, and the position of the Covid-19 PERPPU in the HTN Perspective. This study uses a descriptive method through a normative approach (legal research) to obtain secondary data. The collected data will be analyzed carefully using qualitative analysis or described in sentences. The President's prerogative to issue a PERPPU for handling Covid-19 is contained in Article 22 paragraph (1) of the 1945 Constitution after the amendment which contains provisions on PERPPU which is the President's authority to issue it. The President has the authority to issue a PERPPU in the event of a compelling urgency in an urgent or emergency situation according to the president's own interpretation. PERPPU in